2016
DOI: 10.1128/aac.00808-16
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Profile and Clinical Efficacy of a Novel Hepatitis C Virus NS5A Inhibitor, EDP-239

Abstract: C hronic infection with the hepatitis C virus (HCV) is a major global health burden, infecting approximately 3.5 million individuals in the United States (1) and up to 150 million worldwide (2). HCV is estimated to infect approximately 3 to 4 million people each year, with a prevalence in the United States estimated at 1.3% (1) and prevalences as high as 22% in Egypt, 4.8% in Pakistan, and 3.2% in China (3). Chronic HCV infection can lead to cirrhosis of the liver and hepatocellular carcinoma, contributing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We conducted a placebo-controlled, proof-of-concept study in four cohorts comprised of 6 GT1 HCV-infected patients each. Administration of a single dose of EDP-239 resulted in rapid reductions in GT1a and GT1b HCV RNA levels in patients receiving 10, 30, 100, and 200 mg (14). Deep sequencing of the NS5A gene from GT1a and GT1b clinical viral isolates at baseline discovered many known NS5A RAMs similar to those reported here or elsewhere (15).…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…We conducted a placebo-controlled, proof-of-concept study in four cohorts comprised of 6 GT1 HCV-infected patients each. Administration of a single dose of EDP-239 resulted in rapid reductions in GT1a and GT1b HCV RNA levels in patients receiving 10, 30, 100, and 200 mg (14). Deep sequencing of the NS5A gene from GT1a and GT1b clinical viral isolates at baseline discovered many known NS5A RAMs similar to those reported here or elsewhere (15).…”
Section: Resultsmentioning
confidence: 48%
“…The mutations identified in vitro in this study have been observed in patients that have failed to achieve a sustained virologic response (SVR) following therapy with other NS5A inhibitors (4). However, there was no evidence that these mutations are cross-resistant to other DAA compounds (data not shown) or that previously reported RAMs arising from treatment with DAA compounds are cross-resistant to EDP-239 (14).…”
Section: Discussionmentioning
confidence: 54%
“…Many marketed drugs and compounds in discovery exhibit high PPB levels (Ͼ90%), and physiologically relevant preclinical assays are necessary to make reliable predictions on the impact of PPB (41). The effect of PPB on the in vitro compound activity can be studied by serum shift assays where cells are either cultured in the presence of dilutions of human serum up to 40% or incubated in medium in the presence of physiological concentrations of HSA and hA1GP (12,(42)(43)(44)(45)(46). The latter approach gives more reliable results than using human serum that contains confounding factors such as hormones and growth factors (47).…”
Section: Discussionmentioning
confidence: 99%